2021
DOI: 10.1063/5.0073761
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase transition and giant negative thermal expansion in pyrophosphate Zn2–xMgxP2O7

Abstract: By tuning the structural phase transition in Zn2–xMgxP2O7, large negative thermal expansion (NTE) was achieved at room temperature. An earlier report described that Zn2P2O7 undergoes a structural phase transition at 405 K, accompanied by volume contraction of 1.8% on heating. Results showed that as Mg doping proceeds, the transition temperature decreases. Also, the volume change becomes gradual with respect to temperature. Particularly, Zn1.6Mg0.4P2O7 has a large negative coefficient of linear thermal expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…There are also some materials, although rare, whose volume shrinks with increasing temperature, called negative thermal expansion (NTE) materials . So far, NTE has been reported in many systems such as oxides, cyanides, fluorides, MOFs, and alloys. But to reach precise volume control and avoid thermal shock, the design of zero thermal expansion (ZTE) materials is fundamental in many technological applications such as high-precision instruments and optical and electronic devices . Some ZTE mechanisms and materials were previously reported, for example, a cage-restricting model in Zn 3 GaB 6 O 12 As and Zn 4 P 6 O 12 S, a guest-molecule steric hindrance effect in TiCo­(CN) 6 ·2H 2 O, local structure distortion in (Sc,Fe)­F 3 , a low-frequency phonon compensation effect in Ta 2 Mo 2 O 11 , O atomic perturbations in Sc 1.5 Al 0.5 W 3 O 12 , spontaneous magnetic ordering related to La 0.5 Ba 0.5 CoO 3– x , and so on.…”
Section: Introductionmentioning
confidence: 99%
“…There are also some materials, although rare, whose volume shrinks with increasing temperature, called negative thermal expansion (NTE) materials . So far, NTE has been reported in many systems such as oxides, cyanides, fluorides, MOFs, and alloys. But to reach precise volume control and avoid thermal shock, the design of zero thermal expansion (ZTE) materials is fundamental in many technological applications such as high-precision instruments and optical and electronic devices . Some ZTE mechanisms and materials were previously reported, for example, a cage-restricting model in Zn 3 GaB 6 O 12 As and Zn 4 P 6 O 12 S, a guest-molecule steric hindrance effect in TiCo­(CN) 6 ·2H 2 O, local structure distortion in (Sc,Fe)­F 3 , a low-frequency phonon compensation effect in Ta 2 Mo 2 O 11 , O atomic perturbations in Sc 1.5 Al 0.5 W 3 O 12 , spontaneous magnetic ordering related to La 0.5 Ba 0.5 CoO 3– x , and so on.…”
Section: Introductionmentioning
confidence: 99%
“…The NTE behavior not only exists in 3D framework structure materials, but is also present in 1D or 2D networks, like the NTE behaviors along the MCN (M = Cu, Ag, Au) chain 13 and Ni (CN) 2 , 14 Ta 2 Mo 2 O 11 15 plates, which show 1D and 2D NTE behaviors, respectively. In addition, the NTE properties of some anisotropic materials are improved after sintering into bulk, such as Ca 2 RuO 4 , 16 Zn 1.6 Mg 0.4 P 2 O 7 , 17 and Ti 2 O 3 -based polycrystalline materials. 18 It is found that the flexibility of the crystal structure and transverse vibrations of the bridged atoms govern the NTE behavior in framework structure materials.…”
Section: Introductionmentioning
confidence: 99%
“…13) Zn 2 P 2 O 7 is stable in I2/c (low-T phase, α phase) below 405 K, but it is stable in C2/m (high-T phase, β phase) at higher temperatures. 14) Because the high-temperature phases of Cu 2 P 2 O 7 and Zn 2 P 2 O 7 are both C2/m, it can be reasonably inferred that Cu 1.8 Zn 0.2 P 2 O 7 is in a high-temperature phase of C2/m.…”
mentioning
confidence: 98%
“…10) Among them, pyrovanadate and pyrophosphate represented by A 2 B 2 O 7 (where A represents an alkaline earth metal or transition metal, and B denotes V or P) have recently attracted particular attention. In addition to Cu 2 V 2 O 7 , 11) Cu 1.8 Zn 0.2 V 2 O 7 , 12) Cu 2 P 2 O 7 , 13) and Zn 2-x Mg x P 2 O 7 , 14) research has been expanded to solid solutions between V and P. 15) Particularly, Cu 1.8 Zn 0.2 V 2 O 7 exhibits large NTE with a coefficient of linear thermal expansion (CTE) α L = -14.4 ppm K −1 in a wide temperature T range of 100-700 K, which is assisted by the material microstructural effect peculiar to ceramic bodies. 12) Furthermore, because NTE characteristics comparable to those of bulk materials have been realized even with fine particles of 1-2 μm, 16) they are attracting a great deal of attention as thermal expansion compensators to control the thermal expansion of small areas and microcomponents such as those inside electronic devices.…”
mentioning
confidence: 99%